2016
DOI: 10.1038/ncomms13333
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial viruses enable their host to acquire antibiotic resistance genes from neighbouring cells

Abstract: Prophages are quiescent viruses located in the chromosomes of bacteria. In the human pathogen, Staphylococcus aureus, prophages are omnipresent and are believed to be responsible for the spread of some antibiotic resistance genes. Here we demonstrate that release of phages from a subpopulation of S. aureus cells enables the intact, prophage-containing population to acquire beneficial genes from competing, phage-susceptible strains present in the same environment. Phage infection kills competitor cells and bits… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
138
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 183 publications
(145 citation statements)
references
References 44 publications
(64 reference statements)
1
138
0
Order By: Relevance
“…When serial transfer cultures are initiated with mixtures of sensitive E. coli, virulent and temperate phage, l VIR and l + resistant mutants emerge and ascend to dominate the bacterial population, but both temperate and lytic phage continue to persist along with a minority population of newly formed lysogens. The frequency of these newly formed lysogens is markedly increased if, the addition of low concentrations of kanamycin, which selects for the carriage the l KAN prophage [19,43,44] A recent study showed that temperate phage of P. aeruginosa in the lungs of CF patients carries antibiotic resistance genes and relates to the progression of the disease by providing a selective advantage to their host bacteria [45]. Most importantly, the results of these experiments with combinations of lytic and temperate l indicate that a substantial fraction of the resistant bacteria evolving in these populations are lysogens.…”
Section: Discussionmentioning
confidence: 99%
“…When serial transfer cultures are initiated with mixtures of sensitive E. coli, virulent and temperate phage, l VIR and l + resistant mutants emerge and ascend to dominate the bacterial population, but both temperate and lytic phage continue to persist along with a minority population of newly formed lysogens. The frequency of these newly formed lysogens is markedly increased if, the addition of low concentrations of kanamycin, which selects for the carriage the l KAN prophage [19,43,44] A recent study showed that temperate phage of P. aeruginosa in the lungs of CF patients carries antibiotic resistance genes and relates to the progression of the disease by providing a selective advantage to their host bacteria [45]. Most importantly, the results of these experiments with combinations of lytic and temperate l indicate that a substantial fraction of the resistant bacteria evolving in these populations are lysogens.…”
Section: Discussionmentioning
confidence: 99%
“…[21] There is evidence however that transduction can confer indirect benefits to both phage and lysogen. [22] Spontaneous entry into lysis of prophages from a small number of lysogens generates lytic phage particles which will infect and kill bacteria susceptible to infection. As prophages confer immunity to their lysogenic hosts -called superinfection immunity -susceptible bacteria will be non-lysogens and potentially genetically distinct from the lysogenic host.…”
Section: Temperate Phage As Agents Of Horizontal Gene Transfermentioning
confidence: 99%
“…This process has been observed in Staphylococcus aureus infections as a mechanism for acquiring antibacterial resistance genes from the community, a process termed "autotransduction." [22] As with other mobile genetic elements, temperate phages can themselves encode useful bacterial accessory genes in their own genomes, which then become available for use by the lysogenized bacterial host cell in a process called lysogenic conversion. Lysogenic conversion is best known for its role in pathogen virulence.…”
Section: Temperate Phage As Agents Of Horizontal Gene Transfermentioning
confidence: 99%
“…They can also provide metabolic pathways that improve the host’s competitive edge in different conditions (Bossi et al 2003; Edlin et al 1975, 1977), supply regulatory proteins (Paul 2008), and promote the expression of promiscuous bacterial enzymes (Hultqvist et al 2018). Superinfection exclusion provided by prophages also favors the acquisition of transducing virions that kill sensitive bacteria, increasing the gene transfer to lysogens (Haaber et al 2016; Touchon et al 2017). This includes antibiotic resistance genes (Colavecchio et al 2017).…”
Section: Introductionmentioning
confidence: 99%